How bird clades diversify in response to climatic and geographic factors. (13th July 2017) - Rodríguez‐Castañeda, Genoveva; Hof, Anouschka R.; Jansson, Roland
Abstract: While the environmental correlates of global patterns in standing species richness are well understood, it is poorly known which environmental factors promote diversification (speciation minus extinction) in clades. We tested several hypotheses for how geographic and climatic variables should affect diversification using a large dataset of bird sister genera endemic to the New World. We found support for the area, evolutionary speed, environmental predictability and climatic stability hypotheses, but productivity and topographic complexity were rejected as explanations. Genera that had accumulated more species tend to occupy wider niche space, manifested both as occurrence over wider areas and in more habitats. Genera with geographic ranges that have remained more stable in response to glacial‐interglacial changes in climate were also more species rich. Since many relevant explanatory variables vary latitudinally, it is crucial to control for latitude when testing alternative mechanistic explanations for geographic variation in diversification among clades.